Особенности газификации водоугольного топлива в газификаторах циклонного типа - Пинчук, В. А.; Шарабура, Т. А.; Потапов, Б. Б. (НТУ "ХПИ", 2009)
The analysis of water-coal fuel and its conversion process features was carried out. The results of water-cool fuel gasification-in-stream are presented and environmental scope of problem is discussed. The design features of cyclone-type unit for water-coal fuel gasification are discussed too.
Keywords: уголь; энергетика Украины; водоугольное топливо; композиционное топливо; газификация; циклонный газификатор